2008
DOI: 10.1097/cej.0b013e3282b72093
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of metabolic enzymes CYP1A1, CYP2D6, GSTM1 and GSTT1 and leukemia susceptibility

Abstract: The genetic polymorphisms of biotransformation phase I enzymes, cytochrome P450 (CYP1A1 and CYP2D6), and phase II enzymes, glutathione S-transferase (GSTM1 and GSTT1), were analyzed in 204 healthy persons and 348 leukemia patients, who suffered from also acute lymphoblastic leukemia (ALL), acute nonlymphoblastic leukemia (ANLL) chronic myelogenous leukemia (CML), from the Han ethnic group in Changsha City of Hunan Province of China. Our results showed that the frequencies of polymorphisms of CYP1A1, CYP2D6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 48 publications
(53 reference statements)
1
38
0
3
Order By: Relevance
“…Loureno et al, 2005 reported that in Brazil the individuals with GSTM1 (OR = 0.98; 95% CI: 0.65-1.50), GSTT1 (OR = 1.06; 95% CI: 0.62-1.80) and combined null genotypes (OR = 0.84; 95% CI: 0.36-1.96) are at similar risk of CML as compared with those without the null genotypes (Rollinson et al, 2005). Similar results were also reported by Chen et al, 2008, where no significant difference was observed in the frequencies of GSTM1, GSTT1 or combined genotypes between cases and controls (Chen et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Loureno et al, 2005 reported that in Brazil the individuals with GSTM1 (OR = 0.98; 95% CI: 0.65-1.50), GSTT1 (OR = 1.06; 95% CI: 0.62-1.80) and combined null genotypes (OR = 0.84; 95% CI: 0.36-1.96) are at similar risk of CML as compared with those without the null genotypes (Rollinson et al, 2005). Similar results were also reported by Chen et al, 2008, where no significant difference was observed in the frequencies of GSTM1, GSTT1 or combined genotypes between cases and controls (Chen et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Biotransformation of toxic xenobiotics to their nontoxic forms is considered as the most important step in the processing of the potentially toxic chemical substances toward their elimination [7]. Xenobiotics are metabolized typically in a two-phase reaction: activation and deactivation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that GSTM1 null may affect individual susceptibility to cancer [17]. GSTT1 null has also been proved to be a risk factor for individual susceptibility to some cancers [7,18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the inclusion criteria, 43 studies (Agúndez et al, 1994;Wundrack et al, 1994;Agúndez et al, 1996;Ladona et al1996;Legrand et al, 1996;London et al, 1997;Agúndez et al, 1998;Febbo et al, 1998; González et al, 1998; Hu et Shaw et al, 1998;Krajinovic et al, 1999;Lemos et al, 1999;Topić et al, 2000;Butler et al, 2001;Liu et al, 2002;Sobti et al, 2003;Chen et al, 2004;Fukatsu et al, 2004;Li et al, 2004;Gajecka et al, 2005;Gomes et al, 2005;Guo et al, 2005;Liang et al, 2005;Mochizuki et al, 2005;Sobti et al, 2005;Aydin-Sayitoglu et al, 2006;Bonanni et al, 2006;Li et al, 2006;Lemos et al, 2007;Chen et al, 2008;Khedhaier et al, 2008;Majumdar et al, 2008;Ouerhani et al, 2008 ;Torresan et al, 2008;Yan et al, 2008;Altayli et al, 2009;Gutman et al, 2009;Lim et al, 2011;Luo et al, 2011;Zhou et al, 2011) appeared to have met the inclusion criteria and were subjected to further examination. The flow chart of study selection is shown...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%